2018
DOI: 10.3847/1538-4357/aaa4b9
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitous and Continuous Propagating Disturbances in the Solar Corona

Abstract: A new processing method applied to Atmospheric Imaging Assembly/Solar Dynamic Observatory observations reveals continuous propagating faint motions throughout the corona. The amplitudes are small, typically 2% of the background intensity. An hour's data is processed from four AIA channels for a region near disk center, and the motions characterized using an optical flow method. The motions trace the underlying large-scale magnetic field. The motion vector field describes largescale coherent regions that tend t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 63 publications
0
19
0
Order By: Relevance
“…Both standing and propagating versions of these waves have been found although the standing waves are thought to be locally generated (Wang, 2011;Kumar et al, 2013), whereas the propagating waves originate in the lower solar atmosphere (Jess et al, 2012;Krishna Prasad et al, 2015). Moreover, the propagating waves have been shown to be ubiquitous in the solar corona (Krishna Prasad et al, 2012b;Morgan & Hutton, 2018). A wide range of periodicities are observed, but in general, longer periods (∼ tens of minutes) are dominant in the polar regions (Banerjee et al, 2009b;Krishna Prasad et al, 2011) while the active regions are replete with shorter periods (∼ minutes) (Krishna Prasad et al, 2012a;Wang et al, 2018).…”
Section: Source Of Oscillationsmentioning
confidence: 99%
“…Both standing and propagating versions of these waves have been found although the standing waves are thought to be locally generated (Wang, 2011;Kumar et al, 2013), whereas the propagating waves originate in the lower solar atmosphere (Jess et al, 2012;Krishna Prasad et al, 2015). Moreover, the propagating waves have been shown to be ubiquitous in the solar corona (Krishna Prasad et al, 2012b;Morgan & Hutton, 2018). A wide range of periodicities are observed, but in general, longer periods (∼ tens of minutes) are dominant in the polar regions (Banerjee et al, 2009b;Krishna Prasad et al, 2011) while the active regions are replete with shorter periods (∼ minutes) (Krishna Prasad et al, 2012a;Wang et al, 2018).…”
Section: Source Of Oscillationsmentioning
confidence: 99%
“…The PDs are usually interpreted as slow magnetoacoustic waves, with some studies emphasizing propagation along an open magnetic field (Stenborg et al 2011). The events presented by Morgan & Hutton (2018) were generally fainter compared to these other studies, and PDs were found in closed field structures in an active region and quiet Sun. Sheeley et al (2014) used running difference images and time-distance maps to show "flows" in active regions and within cellular plumes.…”
Section: Introductionmentioning
confidence: 98%
“…This work uses the motion of faint propagating disturbances (PD) in time series of EUV images to gain observational insight into the distribution of the quiet Sun coronal magnetic field. The Time Normalized Optical Flow (TNOF) method to enhance and characterise the PD motions was first described by Morgan & Hutton (2018), with a more simple and efficient approach described by Morgan & Korsos (2022). The amplitudes of the PD are very faint -at most ≈4 DN s −1 , or less than 2% of the background signal.…”
Section: Introductionmentioning
confidence: 99%
“…Compressive oscillations are observed in other coronal structures too (Nakariakov 2006;De Moortel 2009;Banerjee et al 2011). Indeed, they are found to be ubiquitous in open/extended loop structures which are relatively quiescent and cold as compared to the hot flare loops (Krishna Prasad et al 2012;Morgan & Hutton 2018). However, these oscillations are mainly due to driven waves and are believed to be originated in the lower solar atmosphere (Botha et al 2011;Reznikova et al 2012;Jess et al 2012;Krishna Prasad et al 2015).…”
Section: Introductionmentioning
confidence: 99%